ANALISIS KINERJA JALAN PADA PERIODE ARUS MUDIK NATAL (STUDI KASUS JALAN BASUKI RAHMAT KM 7 KOTA SORONG) - Imam Trianggoro Saputro; M.M. Lanny W. Pandjaitan; Lukas (SOSCIED, 2026)
Basuki Rahmat KM 7 Street is one of the main roads in the city of Sorong with a high volume of traffic. Its location in the city center makes this road prone to traffic congestion, especially during rush hour. Therefore, it is crucial to analyze the performance of this road section. The situation becomes even more complex during the Christmas holiday period, when vehicle volume increases significantly, potentially exacerbating traffic congestion. . This study analyzes traffic performance on Basuki Rahmat KM 7 Street during the Christmas holiday using the Indonesian Road Capacity Guidelines (PKJI 2023). The data includes traffic volume, converted into passenger car units (pcu), for both directions—from the regency to the city and vice versa—collected from three days before to three days after the holiday. The analysis looks at traffic volume, degree of saturation (DS), and level of service (LOS). Results show that the highest traffic volumes happen on H-3 and H-1, especially during evening peak hours. The degree of saturation ranges from 0.36 to 0.66, which means traffic is still stable and below maximum capacity. Most of the time, the road operates at LOS C, improving to LOS B on H+3. Overall, Basuki Rahmat Road performs well and can handle traffic changes during the holiday period.